The National Academy of Sciences ‘Clearing the Smoke: assessing the Science Base for tobacco harm reduction’. Washington DC, National Academy Press, 2001 - Hall, Wayne (Addiction (Abingdon, England), 2024)
The 2001 report of the US National Academy of Science on tobacco harm reduction (“Clearing the Smoke”) reviewed the “science base” of tobacco harm reduction (THR) and found that THR was feasible because the epidemiological evidence showed that many of the adverse health effects of cigarette smoking were reduced by substantial periods of abstinence. By 2021, the prevalence of cigarette smoking among US adults had declined to less than half that in 2001. Several new products developed by the tobacco industry have emerged (snus, oral nicotine products, e-cigarettes, heat-not-burn tobacco products), most of which maintain nicotine addiction while reducing the incidence of tobacco-related cancers and cardiovascular diseases.